GAMBARAN PENGETAHUAN DAN MOTIVASI TERHADAP PEMAKAIAN GIGI TIRUAN PADA USIA 40-60 TAHUN DI JALAN KAPTEN MUSLIM HELVETIA KOTA MEDAN - Aminah , Saragih; Desmon Ginola Hutauruk (Poltekkes Kemenkes Medan, 2019)
Oral and dental health is often less a priority for some people, especially in adulthood, teeth can experiencea variety of problems, one of which is date teeth and missing teeth, at that age such teeth that are datedcannot grow back. In overcoming this problem, the use of dentures is one of the right ways. The purpose ofthis study was to determine the description of knowledge and motivation for the use of dentures at age of 40-60 years at Jalan Kapten Muslim Helvetia, Medan City. This type of research is descriptive, where this studywill describe how the description of knowledge and motivation for the use of dentures at age of 40-60 yearsat Jalan Kapten Muslim Helvetia, Medan, February 2019 to May 2019. The sample in this study amountedto 30 peoples aged 40- 60 years old. Data collected are primary and secondary data. Descriptive testing isused to describe the knowledge and motivation of the use of dentures at the age of 40-60 years. The resultsshowed that the level of knowledge of the use of dentures was 56.7% good and 43.3% were moderate. Andthe level of motivation for using dentures was 46.7% (high), 43.3% (medium) and 10% (low). The conclusionafter the research was conducted that the high level of knowledge and motivation for the use of dentures.